Analisis kemampuan representasi matematis berdasarkan self efficacy siswa pada materi fungsi kuadrat - Hasyari, Wan Siti Fatimah Azzahra; Rosmery, Linda; Siregar, Nur Asma Riani (Jurnal Pendidik Indonesia, 2025)
Mathematical representation ability is a critical competency that students must possess to understand and solve mathematical problems, particularly in quadratic functions. This study aims to describe students’ mathematical representation abilities based on their level of self-efficacy. A descriptive qualitative approach was used with six tenth-grade students selected based on their self-efficacy questionnaire results, consisting of two students each from high, medium, and low self-efficacy categories. The research instruments included a self-efficacy questionnaire, a mathematical representation test, and a semi-structured interview guide. The results revealed that students with high self-efficacy were able to fulfill all indicators of mathematical representation—symbolic, verbal, and visual—comprehensively and accurately. Students with medium self-efficacy could meet the three indicators, but with some errors in symbolic representation. In contrast, students with low self-efficacy mostly showed verbal representation ability and encountered difficulties in understanding and converting between visual and symbolic forms. These findings suggest a positive correlation between students’ self-efficacy levels and the quality and completeness of their mathematical representations. Thus, efforts to enhance students' self-efficacy should be considered an essential part of mathematics instruction.